Knowledge and Practice of Menstruation Period Among the Girls at J.S. Murarka Multiple Campus, Lahan (Siraha) (Research Journal on Multi-disciplinary Issues, 2021)
The article highlights knowledge and practice regarding the menstruation period of those girls who are studying at the bachelor level at J.S. Murarka Multiple Campus, Lahan (Siraha). This study is based on primary data. A questionnaire had been prepared to gather information from the students. Altogether 120 girls were purposively selected as the respondents. The result shows that half of the girls (50%) had heard about the menstruation from their mothers and only 4.1 % had received information from books or health-related materials. Likewise, majority- 41.6 % of the students faced lower abdominal pain and discomfort during their first menstruation due to lack of knowledge about menstruation. Among the respondents 12.5 % were only found to be using sanitary pads during their periods. And after use, pads/ materials disposal is challenging in our culture. In our tradition, they still do not burn used pads.